Corrosion-resistant nylon and preparation process thereof

By introducing modified fibers and corrosion-resistant modifiers into nylon composites and adopting specific preparation processes, the problem of insufficient corrosion resistance and processing performance of existing nylon composites in certain applications has been solved, and the corrosion resistance and strength of nylon materials has been significantly improved.

CN119552496APending Publication Date: 2025-03-04NANJING LIHUA ENG PLASTIC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411361982.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In certain specific applications, existing corrosion-resistant, high-temperature flame-retardant nylon composite materials still need to further improve their corrosion resistance and processing performance.

Method used

By introducing modified fibers and corrosion-resistant modifiers, a nylon material including nylon resin, modified fibers, corrosion-resistant modifiers, aluminum trioxide, silicon powder, coupling agents, antioxidants, lubricants, dispersants and binders is prepared, and a specific preparation process includes heating, stirring mixing and melt extrusion.

Benefits of technology

It significantly improves the corrosion resistance and strength of nylon, broadens its application range, and has simple and efficient preparation process, and stable and reliable product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552496A_ABST
    Figure CN119552496A_ABST
Patent Text Reader

Abstract

The preparation process comprises the following steps: step 1, weighing 70 to 90 parts of nylon resin, 15 to 25 parts of modified fiber, 10 to 30 parts of a corrosion-resistant modifier, 6 to 12 parts of aluminum oxide, 6 to 12 parts of silicon powder, 1 to 3 parts of a coupling agent, 1 to 3 parts of an antioxidant, 1 to 3 parts of a lubricant, 1 to 3 parts of a dispersant and 1 to 3 parts of a binder in parts by weight; 2, nylon resin is placed in a heating furnace and heated for 20-30 min at the temperature of 160-200 DEG C, and pretreated resin is obtained; the corrosion-resistant nylon has the beneficial effects that by introducing the modified fiber and the corrosion-resistant modifier, the corrosion resistance and the strength of the nylon are remarkably improved, and the application range of the nylon is widened; the preparation process is simple and efficient, the components are uniformly mixed, and the product performance is stable and reliable; the obtained corrosion-resistant nylon material has wide application prospects in the fields of chemical engineering, electronics, automobiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nylon preparation, and particularly relates to corrosion-resistant nylon and a preparation process. Background Art

[0002] Nylon is an important synthetic fiber material, also known as polyamide fiber; the emergence of nylon material not only gives textiles a new look, but is also a major breakthrough in the synthetic fiber industry and a milestone in the field of polymer chemistry; nylon has good wear resistance, which is unmatched by other fibers; nylon has good heat resistance and can maintain its stable performance under certain high temperature environments; nylon has high mechanical strength and can withstand greater external forces; nylon materials can maintain good toughness and are not easy to break when subjected to external forces.

[0003] Nylon can be used to make swimwear, mountaineering clothes, etc., and is favored because of its wear resistance, easy dyeing and good moisture absorption capacity; in the industrial field, nylon is mainly used in ropes, fishing nets, tire cords, parachutes and engineering plastics, etc. Its high strength and wear resistance make nylon an ideal choice in these fields.

[0004] The patent discloses a corrosion-resistant, high-temperature-resistant and flame-retardant nylon composite material and a preparation method thereof. The patent discloses that the composite material comprises: 30-90 parts of high-temperature-resistant nylon, 0-60 parts of reinforcing fiber, 5-30 parts of brominated flame retardant, 1-10 parts of zinc borate, 0.1-8 parts of silicon powder, 0.1-0.8 parts of antioxidant, and 0.1-0.8 parts of lubricant; the method comprises: mixing dry high-temperature-resistant nylon, brominated flame retardant, zinc borate, silicon powder, antioxidant, and lubricant to obtain a mixture; adding the mixture into the twin-screw extruder from the main feeding port of the twin-screw extruder, adding the reinforcing fiber into the twin-screw extruder from the side feeding port of the twin-screw extruder, and obtaining the corrosion-resistant, high-temperature-resistant and flame-retardant nylon composite material after drawing, cooling, pelletizing and drying.

[0005] Although the patent with publication number CN108250741A provides a corrosion-resistant, high-temperature-resistant and flame-retardant nylon composite material and a preparation method thereof, in certain specific application occasions, its corrosion resistance and processing performance still need to be further improved. Summary of the invention

[0006] The purpose of the present invention is to provide a corrosion-resistant nylon and a preparation process, so as to significantly improve the corrosion resistance and strength of the nylon material.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a corrosion-resistant nylon, comprising the following components in parts by weight: 70-90 parts of nylon resin, 15-25 parts of modified fiber, 10-30 parts of corrosion-resistant modifier, 6-12 parts of aluminum oxide, 6-12 parts of silicon powder, 1-3 parts of coupling agent, 1-3 parts of antioxidant, 1-3 parts of lubricant, 1-3 parts of dispersant, and 1-3 parts of binder.

[0008] As a preferred technical solution of the present invention, the modified fiber preparation method is as follows:

[0009] Select polyester fiber and nylon fiber according to the modification target;

[0010] Plasma treatment, chemical etching, and coating treatment are performed on the fiber surface to increase its ability to bind with other substances or to change its surface properties;

[0011] The modifier is added to the fiber by solution impregnation, spraying, or blending spinning.

[0012] As a preferred technical solution of the present invention, the coupling agent is one of a silane coupling agent and a titanate coupling agent.

[0013] As a preferred technical solution of the present invention, the antioxidant is a thioester.

[0014] As a preferred technical solution of the present invention, the lubricant is one of stearic acid and paraffin.

[0015] As a preferred technical solution of the present invention, the dispersant is sodium hypophosphite, and the binder is polyvinyl alcohol.

[0016] As a preferred technical solution of the present invention, the preparation method of the corrosion-resistant modifier is as follows: tricresyl phosphate, benzotriazole and silicate are placed in a mixer and stirred for 5-15 minutes at 80-120°C and a stirring rate of 400-600r / min to obtain a mixture, and the reaction mixture is filtered, washed and dried.

[0017] The present invention also discloses a corrosion-resistant nylon preparation process, comprising the following steps:

[0018] Step 1: weigh 70-90 parts of nylon resin, 15-25 parts of modified fiber, 10-30 parts of corrosion-resistant modifier, 6-12 parts of aluminum oxide, 6-12 parts of silicon powder, 1-3 parts of coupling agent, 1-3 parts of antioxidant, 1-3 parts of lubricant, 1-3 parts of dispersant, and 1-3 parts of binder according to weight parts;

[0019] Step 2: placing the nylon resin in a heating furnace and heating it at 160-200° C. for 20-30 minutes to obtain a pretreated resin;

[0020] Step 3: Add the pretreated resin, modified fiber, aluminum oxide, and silicon powder into the reactor, stir and mix for 3-5 hours at a stirring rate of 400-600 r / min to evenly disperse the components; then, add the corrosion-resistant modifier, coupling agent, antioxidant, lubricant, dispersant, and binder, and continue to stir and mix for 10-20 minutes to obtain a uniformly mixed mixture;

[0021] Step 4: Add the mixed material into a screw extruder for melt extrusion, then cut the molten material into pellets through a cutting device and dry it.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] By introducing modified fibers and corrosion-resistant modifiers, the corrosion resistance and strength of nylon have been significantly improved, broadening its application range;

[0024] The preparation process is simple and efficient, the components are mixed evenly, and the product performance is stable and reliable;

[0025] The obtained corrosion-resistant nylon material has broad application prospects in the fields of chemical industry, electronics, automobiles, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of the preparation process of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] See also Figure 1 , which is the first embodiment of the present invention, provides a corrosion-resistant nylon, including the following components in parts by weight: 70 parts of nylon resin, 15 parts of modified fiber, 10 parts of corrosion-resistant modifier, 6 parts of aluminum oxide, 6 parts of silicon powder, 1 part of coupling agent, 1 part of antioxidant, 1 part of lubricant, 1 part of dispersant, and 1 part of binder; the coupling agent is a silane coupling agent; the antioxidant is a thioester; the lubricant is stearic acid; the dispersant is sodium hypophosphite, and the binder is polyvinyl alcohol.

[0030] In this embodiment, preferably, the modified fiber preparation method is as follows:

[0031] Select polyester fiber and nylon fiber according to the modification target;

[0032] Plasma treatment, chemical etching, and coating treatment are performed on the fiber surface to increase its ability to bind with other substances or to change its surface properties;

[0033] The modifier is added to the fiber by solution impregnation, spraying, or blending spinning.

[0034] In this embodiment, preferably, the preparation method of the corrosion-resistant modifier is as follows: tricresyl phosphate, benzotriazole and silicate are placed in a mixer and stirred for 15 minutes at 80°C and a stirring rate of 400 r / min to obtain a mixture, and the mixture after the reaction is filtered, washed and dried.

[0035] A corrosion-resistant nylon preparation process comprises the following steps:

[0036] Step 1: weigh 70 parts of nylon resin, 15 parts of modified fiber, 10 parts of corrosion-resistant modifier, 6 parts of aluminum oxide, 6 parts of silicon powder, 1 part of coupling agent, 1 part of antioxidant, 1 part of lubricant, 1 part of dispersant, and 1 part of binder according to weight parts;

[0037] Step 2: placing the nylon resin in a heating furnace and heating it at 160° C. for 30 min to obtain a pretreated resin;

[0038] Step 3: Add the pretreated resin, modified fiber, aluminum oxide, and silicon powder into the reactor, stir and mix for 5 hours at a stirring rate of 400 r / min to make the components evenly dispersed; then, add the corrosion-resistant modifier, coupling agent, antioxidant, lubricant, dispersant, and binder, and continue to stir and mix for 10 minutes to obtain a uniformly mixed mixture;

[0039] Step 4: Add the mixed material into a screw extruder for melt extrusion, then cut the molten material into pellets through a cutting device and dry it.

[0040] Example 2

[0041] See also Figure 1 , which is the second embodiment of the present invention, provides a corrosion-resistant nylon, comprising the following components in parts by weight: 80 parts of nylon resin, 20 parts of modified fiber, 20 parts of corrosion-resistant modifier, 9 parts of aluminum oxide, 9 parts of silicon powder, 2 parts of coupling agent, 2 parts of antioxidant, 2 parts of lubricant, 2 parts of dispersant, and 2 parts of binder; the coupling agent is a titanate coupling agent; the antioxidant is a thioester; the lubricant is paraffin; the dispersant is sodium hypophosphite, and the binder is polyvinyl alcohol.

[0042] In this embodiment, preferably, the modified fiber preparation method is as follows:

[0043] Select polyester fiber and nylon fiber according to the modification target;

[0044] Plasma treatment, chemical etching, and coating treatment are performed on the fiber surface to increase its ability to bind with other substances or to change its surface properties;

[0045] The modifier is added to the fiber by solution impregnation, spraying, or blending spinning.

[0046] In this embodiment, preferably, the preparation method of the corrosion-resistant modifier is as follows: tricresyl phosphate, benzotriazole and silicate are placed in a mixer and stirred for 10 minutes at 100°C and a stirring rate of 500r / min to obtain a mixture, and the mixture after the reaction is filtered, washed and dried.

[0047] A corrosion-resistant nylon preparation process comprises the following steps:

[0048] Step 1: Weigh 80 parts of nylon resin, 20 parts of modified fiber, 20 parts of corrosion-resistant modifier, 9 parts of aluminum oxide, 9 parts of silicon powder, 2 parts of coupling agent, 2 parts of antioxidant, 2 parts of lubricant, 2 parts of dispersant, and 2 parts of binder according to weight parts;

[0049] Step 2: placing the nylon resin in a heating furnace and heating it at 180° C. for 25 min to obtain a pretreated resin;

[0050] Step 3: Add the pretreated resin, modified fiber, aluminum oxide, and silicon powder into the reactor, stir and mix for 4 hours at a stirring rate of 500 r / min to evenly disperse the components; then, add the corrosion-resistant modifier, coupling agent, antioxidant, lubricant, dispersant, and binder, and continue to stir and mix for 15 minutes to obtain a uniformly mixed mixture;

[0051] Step 4: Add the mixed material into a screw extruder for melt extrusion, then cut the molten material into pellets through a cutting device and dry it.

[0052] Example 3

[0053] See also Figure 1 , which is the third embodiment of the present invention, provides a corrosion-resistant nylon, including the following components in parts by weight: 90 parts of nylon resin, 25 parts of modified fiber, 30 parts of corrosion-resistant modifier, 12 parts of aluminum oxide, 12 parts of silicon powder, 3 parts of coupling agent, 3 parts of antioxidant, 3 parts of lubricant, 3 parts of dispersant, and 3 parts of binder; the coupling agent is a silane coupling agent; the antioxidant is a thioester; the lubricant is stearic acid; the dispersant is sodium hypophosphite, and the binder is polyvinyl alcohol.

[0054] In this embodiment, preferably, the modified fiber preparation method is as follows:

[0055] Select polyester fiber and nylon fiber according to the modification target;

[0056] Plasma treatment, chemical etching, and coating treatment are performed on the fiber surface to increase its ability to bind with other substances or to change its surface properties;

[0057] The modifier is added to the fiber by solution impregnation, spraying, or blending spinning.

[0058] In this embodiment, preferably, the preparation method of the corrosion-resistant modifier is as follows: tricresyl phosphate, benzotriazole and silicate are placed in a mixer and stirred for 5 minutes at 120° C. and a stirring rate of 600 r / min to obtain a mixture, and the mixture after the reaction is filtered, washed and dried.

[0059] A corrosion-resistant nylon preparation process comprises the following steps:

[0060] Step 1: Weigh 90 parts of nylon resin, 25 parts of modified fiber, 30 parts of corrosion-resistant modifier, 12 parts of aluminum oxide, 12 parts of silicon powder, 3 parts of coupling agent, 3 parts of antioxidant, 3 parts of lubricant, 3 parts of dispersant, and 3 parts of binder according to weight parts;

[0061] Step 2: placing the nylon resin in a heating furnace and heating it at 200° C. for 20 min to obtain a pretreated resin;

[0062] Step 3: Add the pretreated resin, modified fiber, aluminum oxide, and silicon powder into the reactor, stir and mix for 3 hours at a stirring rate of 600 r / min to evenly disperse the components; then, add the corrosion-resistant modifier, coupling agent, antioxidant, lubricant, dispersant, and binder, and continue to stir and mix for 20 minutes to obtain a uniformly mixed mixture;

[0063] Step 4: Add the mixed material into a screw extruder for melt extrusion, then cut the molten material into pellets through a cutting device and dry it.

[0064] Experimental design was conducted to verify the beneficial effects of this application, and verification was conducted from three aspects: experimental materials, corrosion environment simulation, and corrosion performance test methods. The corresponding contents are as follows:

[0065] Experimental Materials

[0066] Sample A: a sample prepared according to the preparation method of the corrosion-resistant, high-temperature-resistant and flame-retardant nylon composite material described in the reference document CN108250741A;

[0067] Sample B: a nylon sample prepared according to the preparation method provided in this application;

[0068] Corrosion environment simulation

[0069] Select several representative corrosive environments, such as acidic solutions (such as hydrochloric acid and sulfuric acid), alkaline solutions (such as sodium hydroxide solutions), and salt solutions (such as sodium chloride solutions);

[0070] Corrosion performance test methods

[0071] Mass loss method: After placing the sample in a corrosive environment for a period of time, take it out, clean it, and dry it. Then measure its mass change and use the mass loss rate to evaluate the corrosion resistance.

[0072] Electrochemical testing: such as polarization curve testing and electrochemical impedance spectroscopy (EIS), which can provide a deeper understanding of the electrochemical behavior of materials in a corrosive environment;

[0073] Surface morphology observation: Use scanning electron microscope (SEM) or optical microscope to observe the morphological changes of the sample surface before and after corrosion and evaluate the degree of corrosion;

[0074] Record the mass loss rate, electrochemical parameters (such as corrosion potential, corrosion current density) and surface morphology changes of the two samples under each corrosion environment;

[0075] Statistical analysis was performed on the data to compare the corrosion resistance of the two samples under the same corrosion environment;

[0076] The mass loss rate of sample B under the same corrosion environment is lower than that of sample A, and the electrochemical parameters show that its corrosion rate is slower. At the same time, surface morphology observation shows that its corrosion degree is lighter. It is believed that the corrosion resistance of nylon prepared in this application is better than that of the composite material described in the comparative document CN108250741A.

[0077] Although the embodiments of the present invention have been shown and described, as detailed above, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant nylon, characterized in that: The invention comprises the following components in parts by weight: 70-90 parts of nylon resin, 15-25 parts of modified fiber, 10-30 parts of corrosion-resistant modifier, 6-12 parts of aluminum oxide, 6-12 parts of silicon powder, 1-3 parts of coupling agent, 1-3 parts of antioxidant, 1-3 parts of lubricant, 1-3 parts of dispersant and 1-3 parts of binder.

2. The corrosion-resistant nylon according to claim 1, characterized in that: The modified fiber preparation method is as follows: Select polyester fiber and nylon fiber according to the modification target; Plasma treatment, chemical etching, and coating treatment are performed on the fiber surface to increase its ability to bind with other substances or to change its surface properties; The modifier is added to the fiber by solution impregnation, spraying, or blending spinning.

3. The corrosion-resistant nylon according to claim 1, characterized in that: The coupling agent is one of a silane coupling agent and a titanate coupling agent.

4. The corrosion-resistant nylon according to claim 1, characterized in that: The antioxidant is a thioester.

5. The corrosion-resistant nylon according to claim 1, characterized in that: The lubricant is one of stearic acid and paraffin.

6. The corrosion-resistant nylon according to claim 1, characterized in that: The dispersant is sodium hypophosphite, and the binder is polyvinyl alcohol.

7. The corrosion-resistant nylon according to claim 1, characterized in that: The preparation method of the corrosion-resistant modifier is as follows: placing tricresyl phosphate, benzotriazole and silicate in a mixer and stirring and mixing them for 5-15 minutes at 80-120° C. and a stirring rate of 400-600 r / min to obtain a mixture, and filtering, washing and drying the mixture after the reaction.

8. A process for preparing corrosion-resistant nylon according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: weigh 70-90 parts of nylon resin, 15-25 parts of modified fiber, 10-30 parts of corrosion-resistant modifier, 6-12 parts of aluminum oxide, 6-12 parts of silicon powder, 1-3 parts of coupling agent, 1-3 parts of antioxidant, 1-3 parts of lubricant, 1-3 parts of dispersant, and 1-3 parts of binder according to weight parts; Step 2: placing the nylon resin in a heating furnace and heating it at 160-200° C. for 20-30 minutes to obtain a pretreated resin; Step 3: Add the pretreated resin, modified fiber, aluminum oxide, and silicon powder into the reactor, stir and mix for 3-5 hours at a stirring rate of 400-600 r / min to evenly disperse the components; then, add the corrosion-resistant modifier, coupling agent, antioxidant, lubricant, dispersant, and binder, and continue to stir and mix for 10-20 minutes to obtain a uniformly mixed mixture; Step 4: Add the mixed material into a screw extruder for melt extrusion, then cut the molten material into pellets through a cutting device and dry it.

Citation Information

Patent Citations

  • Anticorrosion high temperature resistant and flame-retardant nylon composite material and preparation method thereof

    CN108250741A